2022
DOI: 10.1128/mbio.02739-21
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses Nsp5 Antagonizes Porcine Gasdermin D-Mediated Pyroptosis by Cleaving Pore-Forming p30 Fragment

Abstract: Recently, GSDMD has been reported as a key executioner for pyroptosis. This study first demonstrates the molecular mechanism of pGSDMD-mediated pyroptosis and that the pGSDMD-mediated pyroptosis protects host cells against PEDV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
3
32
0
Order By: Relevance
“…The Nsp5 protease cut human TAB1, the intracellular pattern recognition receptor NLRP12 (Moustaqil et al, 2021), and human gasdermin (Shi et al, 2022).…”
Section: Nsp5mentioning
confidence: 99%
“…The Nsp5 protease cut human TAB1, the intracellular pattern recognition receptor NLRP12 (Moustaqil et al, 2021), and human gasdermin (Shi et al, 2022).…”
Section: Nsp5mentioning
confidence: 99%
“…Overall, the mechanisms by which viruses inhibit pyroptosis remain largely unknown. However, plus sense RNA viruses, such as Coronaviridae, utilize viral proteases to inhibit pyroptosis [182][183][184] (Table 2). Highly conserved viral proteases, such as NSP5 in coronaviruses, directly bind and cleave Gasdermin D in porcine and human cells, producing a truncated N-terminal Gasdermin D, lacking essential residues from caspase-1 cleavage [98].…”
Section: Viral-mediated Inhibition Of Pyroptosismentioning
confidence: 99%
“…More recently, researchers have reported that GZMA from cytotoxic lymphocytes cleaves GSDMB and GZMB from natural killer cells, and cytotoxic T lymphocytes cleave GSDME to trigger pyroptosis in tumor cells [ 37 , 75 ]. Moreover, neutrophil elastase, porcine epidemic diarrhea virus and Cathepsin G directly cleave GSDMD to induce pyroptosis [ 73 , 74 , 93 ]. SpeB also cleaves GSDMA and triggers pyroptosis [ 77 ].…”
Section: Molecular Mechanisms Of Pyroptosis In Ocular Diseasesmentioning
confidence: 99%